(untitled) (Research, Society and Development, 2021)
The family Psychodidae has a cosmopolitan distribution with members that occur in many habitats, mainly in humid environments, and is most diverse in the tropics. Subfamilies Sycoracinae and Phlebotominae have females with hematophagous habits and the latter studied more due to medical and veterinary interest, since it includes species that can transmit diseases to animals and humans. The knowledge about the sand fly fauna in a region is extremely important for adequate monitoring and control measures for leishmaniasis. Thus, the objective of this study was to characterize Psychodidae fauna in relation to richness, abundance and molecular identification of Leishmania spp. in sand flies in southern Santa Catarina, Brazil. The ollections were carried out between 2015 and 2016 in three cities in Santa Catarina, Brazil. Samples were taken near feeding places for domestic animals, urban forest and peridomicile areas. The insects were identified and female sand flies were submitted to molecular analysis to detect the presence of Leishmania spp.. A total of 4,200 insects were collected, 4,193 from the Sycoracinae subfamily and 7 Phlebotominae from the Nyssomyia neivai and Pintomyia fisheri species. Of the studied municipalities, sandflies were registered in Tubarão and Imaruí and the most frequent habitat was the peridomicile areas. No samples were positive for Leishmania spp. In conclusion, the work highlights the presence of two species of sandflies, which were recorded for the first time in southern Santa Catarina.